1990
DOI: 10.1002/jlb.48.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics, Morphology, and Ultrastructure of Human Adherent Lymphokine-Activated Killer Cells

Abstract: Human adherent lymphokine-activated killer (A-LAK) cells represent a population of highly cytotoxic, interleukin-2 (IL-2)-activated peripheral blood lymphocytes that have large granular lymphocyte (LGL) morphology and display natural killer (NK) cell-associated surface markers (CD3-CD56+). The ultrastructure of A-LAK cells also is consistent with that of highly activated NK cells. After their initial isolation, continued culture of A-LAK cells in the presence of IL-2 resulted in cyclic shifts between adherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Lymphocytes activated by IL-2 have an increased expression of adhesion molecules on their cell surface, including integrin subunits and LFA-2 (Melder et al, 1990), and this was confirmed in the present study using flow cytometry. It is unknown whether lymphocytes can recognize specific sites of attachment on the tumour endothelium or whether their attachment is simply physical.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Lymphocytes activated by IL-2 have an increased expression of adhesion molecules on their cell surface, including integrin subunits and LFA-2 (Melder et al, 1990), and this was confirmed in the present study using flow cytometry. It is unknown whether lymphocytes can recognize specific sites of attachment on the tumour endothelium or whether their attachment is simply physical.…”
Section: Discussionsupporting
confidence: 86%
“…These include the architecture of the tumour vasculature (Jain, 1988), the structure and rigidity of in vitro activated lymphocytes (Sasaki et al, 1989) and the expression of adhesion molecules, for example CD 11, CD18 and CD2, on the lymphocyte surface (Melder et al, 1990). Areas within the RENCA tumour possessing bidirectional as well as interrupted flow may have an increased resistance to flow, which may increase the opportunity for lymphocytes to interact with the tumour endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the stack of optical sections pictured in Fig. 2A, podosomes were exclusively located at the ventral surfaces of the cells, indicating that these structures are used by endothelial cells to adhere to the matrix and not to interact with circulating cells (1,25,33). A detailed list of podosome components has been previously established (29), and when investigated, these proteins were found in TGF-␤-induced structures (Table 1).…”
Section: Vol 26 2006 Tgf-␤ Induction Of Podosomes In Endothelial Cementioning
confidence: 63%
“…Using this model, we found that approximately 60% of all human A-NK cells delivered to the isolated colon tumor preparations via the feeding artery remained in the tumor tissue for at least 2-3 h. Therefore, based on this finding, we conclude that the low efficiency of localization of A-NK cells when administered systemically, and probably of other effector cell types as well, is a result of insufficient circulation of the cells and inadequate delivery of cells to the sites of tumor growth. At least four factors may influence the localization of A-NK cells to the tumor: (a) the characteristic irregular morphology of A-NK cells [28]; (b) the increased rigidity of IL-2-activated cells [24]; (c) the architecture and ultrastructure of the tumor vasculature [29]; (d) the expression of cellular adhesion molecules on the surface of A-NK cells [15, 17, 28, 30 -32].…”
Section: Discussionmentioning
confidence: 99%